Profile and perspectives of the first completes of the Licensing Education in the Countryside of the Federal University of Viçosa - Daniela Queiroz do Prado; Lourdes Helena da Silva (Universidade Federal do Norte do Tocantins, 2020)
This study, resulting from research titled "Licensing Education in Countryside of the Federal University of Viçosa" is intended to characterize the first class egresses of the Licensing Education of the UFV (LICENA) as well as the evaluation made by them about the in-course training. These data, collected through the application of questionnaires and interviews revealed that the first class egresses of LICENA is composed by a diversity of countryside subjects, who maintain involvement in various activities in the rural environment, as well as how they integrate peasant social and union movements. In addition, regarding the course evaluation, according to the perspective of the egresses, it stands out that the course proposal still faces challenges, both in the training of countryside educators and in the professional insertion of these subjects in the area proposed by the course.